Pengaruh Brand Image, Influencer, Dan Content Marketing Instagram Terhadap Keputusan Pembelian Produk Kecantikan Scarlett Whitening (Studi Kasus Pada Mahasiswa Tiga Fakultas Besar Universitas Islam Malang) - Popy Hidayanti; Eka Farida; Ita Athia (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This research, which was done on students from the three main faculties of the Islamic University of Malang, intends to identify and assess the influence of brand image, influencers, and Instagram content marketing on the choice to buy Scarlett Whitening cosmetic goods. The research is quantitative in nature. The research sample was collected using a proportionate stratified random sampling methodology or a proportional stratified random sampling method based on the Maholtra formula, which divides the number of indicators by 5, resulting in a sample size of 90 respondents. Multiple linear regression analysis is the data analysis technique used in this investigation. Using the (t test) for partial testing and (F test) for simultaneous testing of the hypotheses. The findings of this study suggest that brand perception, influencer, the choice to buy Scarlett Whitening cosmetic products is significantly influenced by both Instagram content marketing and. Influencers and Instagram content marketing have a substantial impact on buying choices for Scarlett Whitening cosmetic goods, whereas brand image and influencers have a minimal impact. Keywords: Brand Image, Influencer, Instagram Content Marketing, and Purchase Decision